Antimicrobial photodynamic therapy mediated by curcumin-loaded polymeric nanoparticles in a murine model of oral candidiasis - Sakima, Vinicius Tatsuyuji [UNESP]; Barbugli, Paula Aboud [UNESP]; Cerri, Paulo Sérgio [UNESP]; Chorilli, Marlus [UNESP]; Carmello, Juliana Cabrini [UNESP]; Pavarina, Ana Cláudia [UNESP]; De Oliveira Mima, Ewerton Garcia [UNESP] (My University, 2018)
Antimicrobial photodynamic therapy (aPDT) has been proposed as an alternative method for oral candidiasis (OC), while nanocarriers have been used to improve the water solubility of curcumin (CUR). The aim of this study is to encapsulate CUR in polymeric nanoparticles (NPs) and to evaluate its photodynamic effects on a murine model of OC. Anionic and cationic CUR-NP is synthesized using poly-lactic acid and dextran sulfate and then characterized. Female mice are immunosuppressed and inoculated with Candida albicans (Ca) to induce OC. aPDT is performed by applying CUR-NP or free CUR on the dorsum of the tongue, followed by blue light irradiation for five consecutive days. Nystatin is used as positive control. Afterward, Ca are recovered and cultivated. Animals are euthanized for histological, immunohistochemical, and DNA damage evaluation. Encapsulation in NP improves the water solubility of CUR. Nystatin shows the highest reduction of Ca, followed by aPDT mediated by free CUR, which results in immunolabelling of cytokeratins closer to those observed for healthy animals. Anionic CUR-NP does not show antifungal effect, and cationic CUR-NP reduces Ca even in the absence of light. DNA damage is associated with Ca infection. Consecutive aPDT application is a safe treatment for OC.
Keywords: Candida albicans; Curcumin; Keratins; Mice; Nanoparticles; Oral candidiasis; Photochemotherapy